Why do nanowires grow with their c-axis vertically-aligned in the absence of epitaxy? - Azulay, Almog R. (Sci Rep, 2020)
Images of uniform and upright nanowires are fascinating, but often, they are quite puzzling, when the substrate is clearly not an epitaxial template. Here, we reveal the physics underlying one such hidden growth guidance mechanism through a specific example - the case of ZnO nanowires grown on silicon oxide. We show how electric fields exerted by the insulating substrate may be manipulated through the surface charge to define the orientation and polarity of the nanowires. Surface charge is ubiquitous on the surfaces of semiconductors and insulators, and as a result, substrate electric fields need always be considered. Our results suggest a new concept, according to which the growth of wurtzite semiconductors may often be described as a process of electric-charge-induced self-assembly, wherein the internal built-in field in the polar material tends to align in parallel to an external field exerted by the substrate to minimize the interfacial energy of the system.